Cucurbita ficifolia Fruit Extract Induces Tp53/Caspase-Mediated Apoptosis in MCF-7 Breast Cancer Cells. (26th June 2020) - Alshammari, Ghedeir M.; Balakrishnan, Aristatile; Alshatwi, Ali A.; Al-Khalifa, Abdulrahman
Abstract : The second most biggest cancer worldwide is breast cancer. There is an increasing need for safer, effective, and affordable drug candidates from natural sources to treat breast cancer. In the present investigation, the anticancer effect of Cucurbita ficifolia Bouché ( C . ficifolia ) fruit extract was tested on the human breast cancer cells such as MCF-7. The cells were exposed with different doses of C . ficifolia, for the assessment of IC50 concentrations on the MCF-7 cell lines for 24 hs. The effect of C . ficifolia fruit extract on morphological and apoptotic changes were evaluated by specific fluorescence staining techniques and real-time PCR in a time-dependent manner for 24 hs and 48 hs. The IC50 value for C . ficifolia fruit extract was found to be 90 μ g/mL. Morphological alteration and apoptotic distinctiveness aspect like chromatin condensation and nuclear fragmentation were noticed in C. ficifolia extract exposed breast cancer cells. Further, we observed that C . ficifolia extract-induced programmed cell death in the MCF-7 cells were mediated with the elevated expression of the tumor suppressor gene such as p53 and apoptotic markers such as caspase-8, caspase-9, caspase-3, fatty acid synthase (FAS), Fas-associated protein with death domain (FADD), Bcl-2 homologous antagonist/killer (BAK), and Bcl-2-associated X protein (BAX). These observations established that C . ficifolia significantly concealed the cell division and provoked p53/caspase-mediated programmed cell death. Further, we noticed that this cell death in MCF-7 cells is concentration and time dependent. As evaluated through the comet assay, C . ficifolia induced DNA damage; further upon increasing the duration of the treatment, the DNA damage was higher than before. Thus, our study concludes that C . ficifolia could serve as an effective anticancer agent through vital gene modulation.